Reproductive biology of the Caribbean brooding octocoral Antillogorgia hystrix - Coelho, Márcio A.G.; Lasker, Howard R. (Invertebrate biology, 2014)
The reproductive biology of the Caribbean gorgonian Antillogorgia hystrix was studied in the shallow-water reefs of Cross Harbour, Great Abaco (The Bahamas) from 2009 to 2010. Antillogorgia hystrix is an internal brooder that reproduces annually. The population at Cross Harbour was gonochoric and the sex ratio was skewed toward females (∼3:1). Oogenesis precedes spermatogenesis by several months, and lasts at least 9 months, with oocytes >100 μm in diameter first becoming visible in dissections of samples from February; mature oocytes are present in late October–November. The size of mature oocytes (400–900 μm in diameter) was greater than that of the spermaries, which were rarely larger than 400 μm. Brooded planulae were observed in polyps from early November to mid-December, and planula release was observed in aquaria in December 2009, which suggests that planulation occurs continuously over this period. Planulae of A. hystrix contained dinoflagellate symbionts, presumably acquired during embryogenesis and/or by mature planulae while they were in the gastrovascular cavity of the polyp. Brooding is an uncommon reproductive strategy among Caribbean gorgonians and this is the first report of internal brooding in the genus Antillogorgia. The genus contains a number of sympatric species with different modes of reproduction, and knowledge of their reproductive biology is critical to understand their ecology and evolution.